Musical style: flamenco (Journal of Parents and Teachers, 2014)
This article, number nineth of the series “Music and more music” presents Flamenco as a musical style. It talks about the history, the sociocultural context in which it was born, the aim of this music style, the musical characteristics and the main bands and singers. The author chooses a band to work with in the class, and this is Chambao and its song “Papeles mojados” (wet papers) to analayze musically and from an ethic and citizenship point of view.
Keywords: music; music and education; music education; flamenco; class activities.